Educational investments of migrants to Germany – implications for the Skilled Immigration Act - Schuß, Eric [Verfasser] (My University, 2022)
"Integration into the German labour market is often a process which takes several years, even for migrants who have already completed VET or a programme of higher education study abroad. The IAB-SOEP Migration Sample for the years 2013 to 2019 (derived from the annual migration survey carried out by the Institute for Employment Research, IAB, and the German Socio-Economic Panel, SOEP) is used to demonstrate that even these well-qualified groups of persons attend language courses and acquire further qualifications after they have arrived in the country. It also emerges that their participation in education and training is also determined by the legal migration channel used and by career choice as well as being driven by the level of qualification achieved prior to migration." (BIBB-Doku)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; P 1.5 Migranten; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; 370; Zuwanderung; Drittstaat; Fachkräftebedarf; Ausländer; Bildungsbeteiligung; Spracherwerb; Bildungsabschluss; Bildungsinvestition; Berufswahlverhalten